Kinematics of gait using bionic and hydraulic knee joints in transfemoral amputees - Jaroslav Uchytil; Daniel Jandačka; Roman Farana; David Zahradník; Jiri Rosicky; Miroslav Janura (Palacký University Olomouc, 2017)
Background: The development of new technologies has led to further improvements in prosthetic knee joints. Objective: The aim of this study was to compare angle parameters in knee and hip joints during the gait of transfemoral amputees and to determine the effect of the type of knee joint used on their symmetry. The study also compared pelvic movements in transfemoral amputees using different types of knee joints. Method: Eleven patients (5 female, 6 male, mean age 39.2 ± 10.1 years, height 171.8 ± 9.5 cm, mass 71.5 ± 11.0 kg) with a transfemoral amputation (5 used bionic knee, 6 used hydraulic knee) participated in this study. The control group consisted of 10 individuals with no locomotion-related problems (2 female, 8 male). Results: Movement was more symmetrical in the hip joint for all monitored parameters in patients with bionic knee joints. Flexion at heel contact and maximum flexion in the swing phase in the knee joint were more symmetrical in the group with hydraulic knee joints; for all other parameters the group with bionic knee joints achieved better symmetry. The kinematics of pelvic movement in the patients using hydraulic knee joints differed from the control group in all monitored parameters. The greatest difference with excellent effect size (ES = 7.96) was found in pelvic tilt. Pelvic tilt was higher when using hydraulic knee joints. Conclusion:  In comparison with the mechanically passive knee joint, gait with the bionic knee joint evinced gait symmetry.